Togo : Poverty Reduction Strategy Paper-Progress Report-Joint Staff Advisory Note. (IMF Staff Country Reports; Country Report ;, 2011)
The first Annual Progress Report (APR) of Togo highlights many of the reforms implemented during the first year of the Poverty Reduction Strategy Paper (PRSP) while recognizing some weaknesses and implementation constraints. It draws attention to important advances in macrocritical structural reforms, notably in the areas of public financial management; fiscal governance; domestic arrears clearance to private suppliers; and banking sector restructuring. It also presents a macroeconomic framework consistent with the one agreed under the fifth Extended Credit Facility (ECF) review mission. It is recommended that the next APR should elaborate more on the macroeconomic challenges and risks.